Process Modification for Energy Demand Reduction in Acetic Acid Production - Anggita Fauziah Ramadhan; Erike Ultania Saputri; Farica Aprilia Maulida; Hani Maulida; Khayla Anggraini Priyanto (UPT Laboratorium Terpadu, Universitas Diponegoro, 2026)
Methanol carbonylation via the Cativa Process is the dominant technology for acetic acid production, offering high selectivity and operational efficiency. In the initial design of plants based on this process, however, heating energy demand was substantial, particularly during the methanol preheating stage prior to compression, which increased operating costs. Energy optimization is therefore critical to improving the economic viability of the process. This study aims to reduce utility energy demand through modifications in the feed preheating stage. The modification involved installing heat exchangers in the stream supplying the main heater and utilizing the recycle stream as an internal heat source. Simulation results demonstrated a significant reduction in the heating load of the main heater, thereby lowering steam demand compared with the original design. Overall, the total heat load decreased by 102,015.82 kJ/h, equivalent to approximately 22.27% relative to baseline conditions. These findings confirm that simple heat integration in the preheating stage can substantially enhance energy efficiency without compromising process performance. Copyright © 2026 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).